Rhamnolipid As Antifungal Agent Against Pyricularia Oryzae And Rhizoctonia Solani Causing Blast And Sheath Blight Diseases Of Paddy - Shukri, Izah Adlina Mohamad (2024)
Pyricularia oryzae and Rhizoctonia solani are fungi causing blast and sheath blight diseases of paddy (Oryza sativa) in Malaysia. The use of disease resistant rice varieties and fungicides to control both diseases might increase the fungal resistance and the discharge of chemicals into watercourses. This research evaluates the antifungal activity of rhamnolipid, a biosurfactant produced by Pseudomonas aeruginosa USM-AR2 which is more sustainable than chemical fungicides. Seven isolates of Pyricularia sp. and eight isolates of Rhizoctonia sp. from thirty isolates were successfully obtained from blast and sheath blight symptoms in a paddy field in Alor Setar, Kedah, Malaysia. Pathogenicity test confirmed that all Pyricularia sp. and Rhizoctonia sp. isolates were pathogenic by showing a typical blast as an orange brown edge diamond-shaped and sheath blight as an irregular water-soaked. Morphological characterisation and molecular identification of one representative isolate from each group confirmed the identity as P. oryzae USM-PD1 and R. solani USM-PD2. Moreover, antifungal evaluation of rhamnolipid against both fungi demonstrated retarded mycelia with lysis and lesion, as well as slow growth on plates. The highest percentage inhibition of diameter growth (PIDG) for P. oryzae USM-PD1 was achieved at 2000 ppm (48.30 ± 1.18%). Meanwhile, PIDG and percentage inhibition of sclerotia (PISC) number of R. solani USM-PD2 were obtained at 10 000 ppm (60.00 ± 2.35%) and 800 ppm (100%), respectively.